KURIKULUM PEMBELAJARAN BAHASA ARAB TUJUAN KHUSUS PROBLEMATIKA DESAIN DAN IMPLEMENTASINYA DI UIN SUNAN AMPEL SURABAYA - Ahmad Nuruddin; Mirwan Akhmad Taufiq (FASHOHAH, 2021)
This study aims to describe the approach used in the Arabic learning system at State Islamic University of Sunan Ampel Surabaya, so that it can identify the problems in language learning that need to be addressed to date. Because the problems in language learning must continue to be evaluated so that they can achieve the objectives in learning Arabic at State Islamic University of Sunan Ampel Surabaya. In this study using a qualitative method presented descriptively with a type of case study in the Arabic language learning system in an intensive program shaded by the Language Development Center (P2B). Data collection techniques used in this study are participatory observation, interviews, and documentation. The data analysis technique is done by data reduction, data display, and conclusion drawing. The results of this study found some design problems and their implementation in State Islamic University of Sunan Ampel Surabaya which included: (1) Lack of focus on learning objectives. (2) The initial ability test of students is not in accordance with the Arabic language ability test that should be. (3) Short learning time with the material and the target of achieving too much material. (4) Inadequate facilities and facilities. So from this research the researcher provides a solution to overcome some design problems in learning Arabic at State Islamic University of Sunan Ampel Surabaya. Keywords: Arabic language learning, special purpose, communicative